Spatial Cognition and its Relationship to Temporal Cognition among preschool children in Aleppo City - Albader, Yara Barakat; Abdullah, Muhammad Qasim (Journal of Educational and Psychological Sciences, 2022)
The aim of the research is to study the relationship between Spatial Cognition and Temporal Cognition among pre- school children in Aleppo Governorate in Syria, in addition to studying the differences between spatial cognition and temporal cognition according to the gender variable. The research sample consisted of (50) boys and girls between the ages of (3- 6) years. Two tests were used: The Spatial Cognition test and the Temporal Cognition test prepared by the researchers. The study reached the following results: 1) There is a statistically significant relationship between spatial cognition and temporal cognition among pre- school children, 2) There are differences between males and females in spatial cognition in favor of females, 3) There are differences between males and females in temporal cognition in favor of females.